2017
DOI: 10.15287/afr.2016.793
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Natura 2000 network in Romanian Alpine Biogeographical Region: an assessment based on forest landscape connectivity

Abstract: Abstract. Maintaining and increasing landscape connectivity, especially of forest landscapes, are some of the main concerns regarding biodiversity conservation. The connectivity of protected areas for different species represents an indicator for evaluating the effectiveness of the Natura 2000 network. Our research aims to evaluate the connectivity of forest landscapes in the Romanian Alpine Biogeographical Region (ABR) for various terrestrial species. We analysed the distribution of forest patches and Sites o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Assessments of the collaboration degree of different actors have proved to be a useful approach in analyzing the flows of knowledge in developing planning strategies and in the decision-making process. Social network analysis was used in various studies leading to valuable information about the governance of natural protected areas [58][59][60] or urban settings [61]. The network analysis used in our study revealed that enhancing the accessibility of metropolitan residents towards the transportation network is among the top priorities of different stakeholders and public institutions.…”
Section: Discussionmentioning
confidence: 88%
“…Assessments of the collaboration degree of different actors have proved to be a useful approach in analyzing the flows of knowledge in developing planning strategies and in the decision-making process. Social network analysis was used in various studies leading to valuable information about the governance of natural protected areas [58][59][60] or urban settings [61]. The network analysis used in our study revealed that enhancing the accessibility of metropolitan residents towards the transportation network is among the top priorities of different stakeholders and public institutions.…”
Section: Discussionmentioning
confidence: 88%
“…The Natura 2000 network is an important biodiversity conservation measure [11], and consists of different types of protected areas: the terrestrial Special Protection Areas (SPA, for bird protection only), the terrestrial Sites of Community Importance, and Special Areas of Conservation (SCI and SAC, for habitats and/or species) [59]). In addition to, but partly overlapping with the Natura 2000 network, Romania also implemented protected areas designated as natural and national parks as well as biosphere reserves [48].…”
Section: Study Regionmentioning
confidence: 99%
“…It is important to stress, however, that our evaluations by no means suggest that the current network of PAs is sufficient. Around 23% of Romania's land surface area is currently under protection, and improvements to the protected area network may be necessary [48,49]. Large ecoregions and several widespread bird and mammal species may be protected sufficiently well, but smaller ecoregions, as well as invertebrate and plant species are for example underrepresented in the existing Natura 2000 network [49].…”
Section: Representation In Existing Protected Areas and Conservation Implicationsmentioning
confidence: 99%
See 2 more Smart Citations